Hidden Benefits of Reward: A Field Experiment on Motivation and Monetary Incentives - Ola Kvaløy; Petra Nieken; Anja Schöttner (Center for Economic Studies and ifo Institute (CESifo), 2013)
We conduct a field experiment in a controlled work environment to investigate the effect of motivational talk and its interaction with monetary incentives. We find that motivational talk significantly improves performance only if it is accompanied by performance pay. Moreover, performance pay reduces performance unless it is accompanied by motivational talk. By adding motivational sentences to an otherwise neutral explanation of the work task, the effect of performance pay goes from slightly negative to significantly positive. Hence, we find what we call a hidden benefit of monetary rewards: complementarity between performance pay and motivational talk.
Keywords: C93; M52; J33; 330; verbal motivation; performance pay; field experiment